Micro-jet formation induced by the interaction of a spherical and toroidal cavitation bubble - Jaka Mur; Alexander Bußmann; Thomas Paula; Stefan Adami; Nikolaus A. Adams; Rok Petkovsek; Claus-Dieter Ohl (Ultrasonics Sonochemistry)
We investigate experimentally and numerically the interaction between a spherical cavitation bubble and a wall-bounded toroidal cavitation bubble. We demonstrate that shock wave focusing following toroidal bubble initiation induces the formation of micro-jets that pierce the spherical bubble in the torus-axis direction away from the surface, strongest in the anti-phase scenario. The velocity of micro-jets is determined by the initial standoff distance of the spherical bubble from the wall and thus from the toroidal bubble, with peak jet velocities approaching 1000m/s. The micro-jets are triggered by the complex interaction between the torus shock wave and the surface of the spherical bubble. Additionally, the formation of secondary cavitation appears to significantly enhance the micro-jets compared to scenarios without secondary cavitation. Following the formation of micro-jets, a subsequent broad jet pierces the spherical bubble, marking the onset of its collapse. After the collapse, we observe an amplified rebound phase resulting in a more than twofold increase of the bubble volume compared to the initial bubble.